(untitled) (Khairulummah, 2025)
This study investigates the various interpretations of the Periklytos within Muslim and Christian intellectual heritage and examines how these understandings can contribute to fostering interreligious harmony. In Christian theology, the Periklytos primarily identified with the Holy Spirit in the Gospel of John, serves as a divine advocate, comforter, and guide for believers. In Islamic literature, however, classical and modern commentators have explored alternative interpretations, with some associating the Periklytos with prophetic references to the coming of the Prophet Muhammad (SAW), while others frame it within broader concepts of divine support and revelation. Through a comparative analysis of scriptural sources, linguistic studies, early theological writings, and subsequent scholarly debates, this study highlights both the convergences and divergences in the ways Muslims and Christians have understood the Periclytos across history. It also situates these interpretations within their respective intellectual heritages, showing how historical interactions, polemics, and dialogue shaped the development of each tradition’s perspective.